2014
DOI: 10.1563/aaid-joi-d-12-00014
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Implant Stability Measurements Based on Resonance Frequency Analysis After Placement in Healed or Regenerated Bone

Abstract: Primary stability is an indicator of subsequent osseointegration of dental implants. However, few studies have compared the implant stability among anatomical regions and bone types; thus, not enough data exist regarding the stability of implants placed in regenerated bone (RB). The present study evaluated primary and long-term stability of implants placed in RB and non-regenerated healed bone (HB). A total of 216 screw cylinder implants were placed in 216 patients (98 in HB and 118 in RB, 6 [RB6, N = 68] or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…13 Many comparative studies of bone regeneration and implants are based on their stability. 28,29 In a study by Deli et al, 30 implants placed in sites of bone regeneration were found to offer less stability. However, stability is not the only implant characteristic examined in relation to bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…13 Many comparative studies of bone regeneration and implants are based on their stability. 28,29 In a study by Deli et al, 30 implants placed in sites of bone regeneration were found to offer less stability. However, stability is not the only implant characteristic examined in relation to bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…RFA is an objective, noninvasive, reliable, predictable modality for the measurement of implant stability ( 9 ). Huwiler et al ( 10 ) found that the ISQ values of successfully placed implants during healing period were between 57 and 70.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be the macrogeometry of the implant used: with a self-cutting and self-tapping design, the novel implant was capable of reaching an excellent primary stability in all clinical situations. According to Deli et al [46], ISQ values in the maxillary premolar area were statistically significantly (p > 0.05) higher in regenerated sockets compared to healed sites.…”
Section: Discussionmentioning
confidence: 95%